Chinese sociotechnical imaginaries of earth observation: from sight to foresight - Bennett, Mia M. (Big data & society, 2023)
Although Earth observation (EO) is considered a universal scientific technique with a hegemonic gaze, national sociotechnical imaginaries shape its practice. Historically established and organized by national governments, EO, which is commonly pursued via satellite remote sensing, depends on domestic perceptions of the technique's scope and applications. EO is also a political technology with the capacity to mediate and potentially regulate life on Earth at a range of scales. In China, the state and scientists endeavor to transform EO into a data-driven, inductive, and predictive method with a focus on social coordination, especially in cities—a key scale for scientific study and the organization and reproduction of state power. Contributing to China's reimagining of EO as a governance and governmentality tool are advances in social sensing, which leverages big data continuously generated by individuals’ devices. By analyzing big EO and social data, rather than only observe past and present changes to the Earth's surface, the Chinese state and scientists seek to predict future social events. While these changes are narrated as a popularization of remote sensing enabling more responsive, human-centric governance, they may augur the rise of antipolitical technologies that attempt to prevent dissent by determining and even guiding future behavior. As China, a satellite power, aims to export its services for observing and predicting Earth and upscale them through global governance, critique of their associated sociotechnical imaginaries is crucial. Such research reveals the heterogeneity of the satellite gaze and may identify where and how people hold power within EO systems.
Gesehen am 11.10.2023